Giant prolactinoma case with side effects due to cabergoline - Çalkaya, Semiha; Bayram, Fahri; Kurtsoy, Ali; Dursun, Hüseyin (Archives of Case Reports, 2020)
Dopamine agonists should usually be the first treatment for patients with prolactinomas of all sizes, because these drugs decrease serum prolactin concentrations and decrease the size of most lactotroph adenomas. Cabergoline is preferred first. When cabergoline develops side effects bromokriptin is switched. Cabergoline is more efficient than bromocriptine. Its side effect profile more favorable than bromocriptine. Cabergoline is an ergot dopamine agonist that is administered once or twice a week. Cabergoline can have rarely serious psychiatric adverse effects, including psychosis, impulse control disorders, dyskinesia, pulmonery fibrosis and valvular heart disease. Prolactinomas are the most common pituitary tumors, 93%-95% of the cases are microadenomas. Macroprolactinomas larger than 40 mm, known as giant prolactinomas, are exceptionally rare, accounting for 0.5% - 4% of all prolactin-hypersecreting adenomas. In our case, after the 7 x 6 cm giant macroprolactinoma operated we report the manic episode occuring during the second week of cabergoline treatment. In the treatment of patients with prolactinoma, cabergoline is a first choice drug because it has a better tolerance profile and is more effective, however, bromocriptine can be switched to when drug resistance or side effects develop to cabergoline.